Modeling and Assessment of a Biomass Gasification Integrated System for Multigeneration Purpose - Shoaib Khanmohammadi; Kazem Atashkari; Ramin Kouhikamali (International Journal of Chemical Engineering)
The use of biomass due to the reduction in greenhouse gas emissions and environmental impacts has attracted many researchers’ attention in the recent years. Access to an energy conversion system which is able to have the optimum performance for applying valuable low heating value fuels has been considered by many practitioners and scholars. This paper focuses on the accurate modeling of biomass gasification process and the optimal design of a multigeneration system (heating, cooling, electrical power, and hydrogen as energy carrier) to take the advantage of this clean energy. In the process of gasification modeling, a thermodynamic equilibrium model based on Gibbs energy minimization is used. Also, in the present study, a detailed parametric analysis of multigeneration system for undersigning the behavior of objective functions with changing design parameters and obtaining the optimal design parameters of the system is done as well. The results show that with exergy efficiency as an objective function this parameter can increase from 19.6% in base case to 21.89% in the optimized case. Also, for the total cost rate of system as an objective function it can decrease from 154.4 $/h to 145.1 $/h.